Renewable Energy Toolkit Needs Assessment - Cabraal, R. Anil (World Bank, Washington, DC, 2014)
There is now a strong foundation of good practice emerging from past and ongoing renewable energy (RE) projects, whether supported by the WBG or others, making it possible to develop and implement future projects faster, at lower costs, and with greater confidence in their overall sustainability. To further this process, the World Bank plans to develop an "Operational Guide to Design and Implement Renewable Energy," which will provide the necessary tools to assist Bank staff and member country personnel in improving the design and implementation of RE projects. This operational guide will help to significantly reduce project preparation cost and preparation time and increase project success. Developing the RE toolkit consists of two phases: phase I, a scoping study and need assessments, and phase II, developing the RE toolkit. This report summarizes the findings from phase I. It consists of the following four sections, which are the major activities undertaken under phase I : a) need assessment with the World Bank Group task managers; b) need assessment with RE industries and financial institutions; c) inventory research of previous work on toolkits related to rural energy and renewable energy; and d) development of a conceptual framework and a proposal for phase II.